Hydraulic Fracturing Mechanism of Rock Mass under Stress-Damage-Seepage Coupling Effect - Zhengzheng Cao; Yue Wang; Haixiao Lin; Qiang Sun; Xiaogang Wu; Xiaoshuai Yang (Geofluids)
According to the damage evolution model of rock mass under stress-seepage coupling effect, the representative element theory is employed to describe the change law of rock mesostructure. Based on the theory of elasticity and Weibull distribution, the statistical damage constitutive model of rock mass and the finite element numerical algorithm are established, by adopting the COMSOL Multiphysics numerical software and MATLAB program. Besides, the validity of the statistical damage constitutive model of rock mass is verified by the triaxial compression test. Besides, the hydraulic fracturing processes of rock mass under equal and unequal in situ stresses are numerically simulated, and the mechanical behavior of rock mass during hydraulic fracturing in complex underground environment is also studied. Under the condition of equal in situ stress, the stress distribution of surrounding rock of circular hole is annular, which is similar to the elastic stress distribution of surrounding rock. Under the condition of unequal in situ stress, the stress distribution tends to be circular with the increase of lateral pressure coefficient, and the stress distribution along the diagonal decreases. The simulation results are in good agreement with the theoretical results, which indicates that the damage mechanical model and the numerical model have correlation and certain accuracy. By analyzing the size and direction of horizontal in situ stress, the shape and extension direction of cracks are judged, which provides an important theoretical basis for water inrush prediction and engineering protection.